IMPLEMENTATION OF LAND REGISTRATION IN PROVIDING LEGAL CERTAINTY OVER LAND RIGHTS IN JAYAPURA CITY - Pabassing, Yulianus (Awang Long Law Review, 2022)
This study aims to find out how the implementation of land registration in providing legal certainty of land rights in Jayapura City and understand what factors hinder the system of implementing land registration to obtain legal certainty of land rights in Jayapura City. This research was conducted in Jayapura City as the capital of Papua Province. The city of Jayapura is seen as a service city and still has land issues, namely regarding the sale and purchase of land. The results of the study show that the implementation of land registration in order to provide legal certainty of land rights in Jayapura City is carried out in two ways, namely sporadic, that is, individual registration is carried out. Meanwhile, the factors that led to the implementation of land registration in Jayapura City not complying with regulations were: a) collection of juridical data and physical data; b) incomplete facilities and infrastructure; c) low integrity of the apparatus, and d) low awareness of the community itself. To understand how the implementation of land registration in providing legal certainty of land rights in Jayapura City requires legal counseling that is directly delivered by extension agents to the public, either through printed media (such as banners, brochures, leaflets).